Factors Affecting Employee Loyalty: Lessons From Millennials Working In E-Commerce Companies In Jakarta - Jasmine Jemilia Maulidiani; Risa Bhinekawati (Jurnal Administrasi dan Kesekretarisan, 2020)
A large middle-class group of Indonesia is predominantly made up of millennials, who are vastly becoming the majority of the workforce, especially leading the Indonesian digital technology industry. Studies have shown that millennials tend to have a higher turnover rate than other generations . A substantial amount of studies and research analyzing the factors affecting employee loyalty have been conducted worldwide, with different scopes. Factors such as trust in management, trust in peers, and empowerment, with the mediating variable of employee satisfaction, have also been studied and found to have considerable effect on employee loyalty. To extend previous research, this study investigates the effect of trust in management, trust in peers, and empowerment on employee satisfaction as an intervening variable, and the effect of employee satisfaction on employee loyalty. This quantitative research analyzes the causal relationships between the variables mentioned by surveying a total of 100 millennial employees of e-Commerce companies in Jakarta as respondents. The study finds that that trust in management and empowerment have have positive and significant effect on employee satisfaction, and subsequently on employee loyalty. However, trust in peers does not have impact on employee satisfaction and subsequent employee loyalty. Theoretically, the result of this research strengthens the findings of previous studies on the relationships among the observed variables, in the context of e-commerce millennial employees, in Jakarta. Practically, companies in Jakarta in developing human resources management strategies to attract and retain millennial employees by understanding the factors affecting their employee satisfaction and employee loyalty.